Tinjauan yuridis tentang ketenagakerjaan terhadap pemutusan hubungan kerja akibat dampak Covid-19 - Antonius Bogar; Ukas Ukas (University of Merdeka Malang, 2021)
The Indonesian Manpower Law act Number 13 of 2003 concerning Manpower regulates in detail the termination of employment (PHK) as well as legal protection for workers who are laid off. In terms of employment, which is a critical issue at this time is the Termination of Employment (PHK) of workers/laborers because companies are hit by the Covid-19 Pandemic. This research includes normative legal research with a statutory approach and in the analysis of legal materials using qualitative descriptive techniques. In this study, the main problem that the author examined is the legal basis for dismissal based on the Covid-19 Pandemic and the legal consequences for workers who work under a work agreement (PKWT). Based on the research problems and methods, the results of this study found that the termination of employment (PHK) committed against workers since the Covid-19 pandemic was a violation, therefore it is an act against the law and against the law. As a consequence, the company is obliged to pay the rights of workers/labor in accordance with the provisions and regulations of the prevailing laws.How to cite item: Bogar, A., Ukas, U. (2021). Tinjauan yuridis tentang ketenagakerjaan terhadap pemutusan hubungan kerja akibat dampak Covid-19. Jurnal Cakrawala Hukum, 12(3), 245-253. doi:https://doi.org/10.26905/idjch.v12i3.7097